The Role of Epigallocathecin-3-gallate as an Antioxidant After Dental Bleaching on Shear Bond Strength of Composite Resin Restoration - Syarifah Nadhira Assyafira Al-Habsyi; Kun Ismiyatin; Galih Sampoerno (Universitas Airlangga, 2021)
Background: Tooth discoloration can be treated with dental bleaching using Hydrogen peroxide (H2O2). Dental bleaching may interfere with the shear bond strength of composite resins because the remaining free radicals can affect bonding polymerization. Epigallocatcehin-3-gallate (EGCG) as an antioxidant can neutralize the free radicals produced during bleaching process. Purpose: Analyze the role of EGCG antioxidants in increasing the shear bond strength of composite resin after bleaching.. Reviews: Of the seven journals included in this literature review, six journals reported significant difference, and one journal noted no significant difference in the shear bond strength of composite resin following the EGCG application. Conclusion: The use of EGCG can increase the shear bond strength value of post-bleaching composite resin restorations.